Financial Distress Testing Model To Audit Report Lag - Erma Setyowati; Chania Aulia; Fatchan Archyani (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose:This research uses the audit committee as a moderating variable to examine how the financial crisis, solvency, and complexity of corporate operations are tested on Audit Report Lag. Methodology/approach:Facilities and infrastructure firms listed on the Indonesia Stock Exchange (IDX) in 2019–2022 make up the study's population. The sample consisted of up to 32 enterprises that were chosen via deliberate sampling. Modified Regression analytical (MRA) is the term for the analytical method. Findings:The study's findings indicate that solvency and financial difficulties have a big impact on audit report lag. In the meanwhile, Audit Report Lag is not significantly impacted by the complexity of the company's operations. The audit committee does not moderate the relationship between solvency, financial stress, and the intricacy of the corporate operations on Audit Report Lag. Practical Implication:By paying attention to the variables that affect audit report delay, investors can use the findings of this study to optimize their investment decision making. In addition, can also help auditors to complete audit reports with less time, accuracy, and quality. Originality/value:This study is unique and valuable because it employs multiple linear regression models, a broad theoretical framework, new moderating variables, extensive secondary data, sophisticated statistical analysis, and a discussion of relevant limitations and recommendations. The findings of this study can further our understanding of the connections between financial distress, solvency, operational complexity, audit committee, and audit report lag. They can also further the advancement of financial and auditing theory and practice